Food Safety and Social Risk in Contemporary China - Yan, Yunxiang (The Journal of Asian studies, 2012)
Food-safety problems constitute a new, urgent, and multifaceted challenge to Chinese people, society, and the state, involving a number of social, political, and ethical issues beyond those of food safety, nutrition, and health. In light of Ulrich Beck's theory of risk society, this article examines food-safety problems in contemporary Chinese society at the levels of food hygiene, unsafe food, and poisonous foods and argues that food-safety problems not only affect the lives of Chinese people in harmful ways but also pose a number of manufactured risks that are difficult to calculate and control. More importantly, food-safety problems in China have contributed to a rapid decline of social trust, thus posing a risk of distrust that has far-reaching social and political ramifications. In this sense, a risk society has already arrived in China but it comes with certain local characteristics and poses some new theoretical questions.